Willingness to accept human papillomavirus vaccination in Jimma town, Ethiopia - Tsegaw Biyazin; Aynalem Yetwale; Belete Fenta (Taylor & Francis Group, 2022)
Vaccination against HPV is effective against cervical cancer, and the success of HPV vaccination is determined by the willingness to accept the vaccine. Therefore, the purpose of this study was to assess willingness to be vaccinated among female high school students, in Jimma town, Ethiopia. A cross-sectional study was conducted with female high school students in Jimma town, Ethiopia. Study participants were selected using a simple random sampling method. Data were collected using a self-administered method. Data were entered using Epi-data version 3.5, exported, and analyzed using the statistical package for the social sciences (SPSS) version 21. Pearson's chi-square test was used for data analysis. Finally, the results were narrated using text, tables, and graphs. A total, of 366 study participants were interviewed and yielded a response rate of 94.8%. The majority of responders (267 or 72.9%) belonged to the age class 16-20 years. Two-thirds 68.9% of respondents were willing to take HPV vaccines. Respondents' mother education (P = .041), respondents who had an older sister (P = .014), who had a smartphone (P = .043), knowledge (P = .001), and attitude (P = .006) variables were significantly associated with willingness to accept HPV vaccine. Only two-thirds of the study participants were willing to vaccinate. Responders' mother education status, responders who had an older sister, smartphone, good knowledge, and a favorable attitude toward HPV vaccine were significantly associated with HPV vaccine acceptance. All concerned bodies have to enhance the willingness of the target population to take HPV vaccination.